О ведущей группе слов умственной характеристики в бурятском языке: On the leading vocabulary group of the mental characterization in the Buryat language - Л. Д. Бадмаева (Acta Mongolica, 2005)
On the basis of a "spectrum" of the lexical meanings there are revealed sematic relations forming subgroups in the leading group of the mental vocabulary of the Buryat language making a synonymous now. It is shown a derivative character of the members of this synonymous row by a structural and grammatical description.